‘Ça tient qu'à toi’: cartographies of post-fordist labour in Laurent Cantet's L'Emploi du temps - Marks, John (Taylor & Francis, 2011)
Drawing on Gilles Deleuze's work on Michel Foucault, control societies and cinema, Laurent Cantet's L'Emploi du temps is analysed as a cartographic rendering of post-Fordist labour. The film creates a pervasive ambiance of liminality and dreamlike disconnection—‘flottement’—around the central character of Vincent in order to convey the affective landscape of post-Fordist immaterial labour (in this case business consultancy). Approaching L'Emploi du temps as a diagram—in Deleuzian terms—of discursive and non-discursive components helps to explain the ways in which the film goes beyond psychoanalytic drama in order to convey a more general sense of a social reality that is frequently problematic and overwhelming for Vincent. Recent work on hypermodernity and the hypermodern self is employed in order to analyse Vincent's behaviour as an example of the kinds of subjectivity produced by control societies. In many cases, the hypermodern individual is fragile, isolated and unpredictable, prone to excessive behaviours and periodic breakdowns. Whereas Cantet's previous film, Ressources humaines, powerfully dramatised a crisis of place, L'Emploi du temps conveys an individual and collective crisis of confidence.